The Course Review Horay Learning Model: Its Effectiveness on the Indicator of Self-Confidence in One's Abilities - Adilah Afanin; Mar’atuzzakiyyah Mar’atuzzakiyyah; Malsha Shofa Papat Limo; Muhammad Haikal El-Khoiri Nazrika; Mahfudh Shodiq; Nurul Azizah (PT. Pusmedia Group Indonesia, 2025)
This research was motivated by the low level of students’ self-confidence, which is partly due to the continued use of conventional teaching methods. The aim of this study is to determine whether there is a significant difference in the effect of the Course Review Horay learning model on students' self-confidence in Islamic Religious Education (PAI) at SMAN 12 Bandar Lampung. This study used a quantitative approach with a Quasi-Experimental Design. The sampling technique used was simple random sampling, as it is considered fair and minimizes bias, giving all students an equal chance to be selected. The population of this study consisted of all Grade X students, totaling 341 students. The selected sample consisted of Class X.KP.1.1 with 33 students as the experimental group, which used the Course Review Horay model, and Class X.KP.1.2 with 32 students as the control group, which used the conventional learning method. Data were collected using a self-confidence questionnaire. The data analysis technique used was a simple analysis method to examine the relationship between the independent and dependent variables. The results of the Independent Samples T-Test showed a significance value of 0.000 < 0.05, indicating that the Course Review Horay model is significantly more effective in improving students’ self-confidence compared to the conventional method. This study contributes to the development of innovative learning models, especially in the field of Islamic Religious Education. The implementation of the cooperative-based Course Review Horay model creates a more supportive learning environment, thus playing an important role in enhancing students' self-confidence.